Kinematics & stellar populations of nearby bulges - Falcon Barroso, Jesus (2003)
In this thesis, we investigate the internal kinematics and stellar populations of a subsample of the bulges of nearby galaxies defined by Balcells & Peletier (1994). To do that we have analysed minor axis spectroscopic data of the sample together with Integral Field observations of one the most interesting galaxies in it (NGC7332).